The Effect of Fiscal Services and Tax Socialization on Taxpayer Compliance (Case Study of MSMEs in Palembang City) - Ridho Al Safero; Harsi Romli; Emilia Gustini (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to inspect the effect of tax administration services and tax socialization on taxpayer compliance on SMEs in Palembang. The sample was selected using the Simple Random Sampling technique. Data for 100 respondents were collected through a questionnaire which was then analyzed using multiple linear regression. The result evinces that tax authorities' service, and tax socialization have an effect on the taxpayer compliance variable. The results of the analysis show that simultaneously the tax authorities' service variable and tax socialization have an effect on the taxpayer compliance variable. This research is expected to provide benefits for the government to pay more attention to tax authorities and tax socialization services to increase compliance with taxpayers of SMEs in Palembang City.